Tingkat Spiritual Quotient Mahasiswa Generasi Z dalam Mengimplementasikan Pendidikan Karakter - Fauziah, Fauziah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2024)
The heterogeneity of generation Z students in Malang Raya forms a varied attitude so that the level of spiritual quotient experiences serious things that must be considered. In fact, this intelligence will shape the direction of character education in accordance with the values contained therein. In this regard, the purpose of this study is to analyze the level of spiritual quotient and its orientation towards character education of Malang Raya students. The approach used in this study is a quantitative approach with a survey research type at four PTKI in Malang Raya. Data were obtained from the results of distributing questionnaires and tests on spiritual quotient. The results of the study showed that the level of spiritual quotient of Malang Raya students was: 32% high, 62% moderate, 6% low with a mean of 85.07 which means that the level of spiritual quotient of students is good, while the orientation of spiritual quotient towards character education is seen in the wisdom taken from every incident and disaster experienced, always keeping promises, trying to apologize and giving happiness to others. The findings of this study are that character education requires strengthening the spiritual quotient in students so that religious values ​​can truly be applied internally and externally to the self and mentality of each student.